(untitled) (Wudil Journal of Science and Technology Education, 2025)
This paper examines the United States–China trade war through the lens of Huawei Technologies, focusing on the intersection of trade, technology, and geopolitical rivalry. Using a qualitative approach to secondary data, the study situates Huawei at the epicenter of a contest over fifth-generation (5G) telecommunications infrastructure and its strategic implications. Drawing on the mercantilist tradition and the contemporary framework of techno-nationalism, the paper argues that Huawei’s rise as a global technology leader has amplified U.S. concerns over economic security, intellectual property, and global influence. Findings suggest that the trade war has resulted in significant trade diversion, export losses, and shifts in global supply chains, while reinforcing a new era of “weaponized interdependence” in international relations. The paper concludes that the Huawei case illustrates how advanced technologies now function not only as economic assets but as geopolitical bargaining chips in great power competition.The paper explores the United States-China trade war through the lens of Huawei while focusing on trade, geo politics, technology and history of long political rivalry. The paper will use qualitative approach in secondary data, the study explains how Huawei a Chinese Tele-communication giant and a pioneer of the 5G technology found its self at the epicenter of this conflict as well as the implications. The economic theory of mercantilism will be utilized as a framework in explaining techno-nationalism. The paper argues that the rise of Huawei has a global tech leader has prompted US concern over intellectual property right, privacy, security, economic security as well as security and surveillance. This sheds light of the dynamic shift of global influence from the Western Block (US) to the Eastern Block (China). The Trade war has resulted in significant trade diversion, shifts in supply chain and economic sabotage while reinforcing a new “weaponized interdependence” in International relations. Finally, the case of Huawei illustrates how the advanced technologies now function not only as economic assets, but also as bargaining chips. The age of warfare has changed significantly post 1945, armored tanks; gun and ammunition has been replaced with cyber warfare and economic warfare. The 21st Century presents a different style of warfare among nation, this study carefully highlights that. The back- bone of every nation is its economy, wealth means power in international relations, and the trade war is simply a nation’s pursuit of its National interest/Foreign policy.